Stability of equilibrium in upright stance and voluntary motion control in athletes-shooters in the process of ready position and target shooting - Pryimakov, A. A.; Eider, E.; Omelchuk, E. V. (Physical Education of Students, 2015)
Purpose: consists in studying the relationships between the system of equilibrium regulation in upright stance and voluntary motion control in athletes-shooters during ready position and target shooting. Material: 19 highly skilled athletes specialized in pistol shooting were studied. Physiological and biomechanical characteristics of posture and voluntary motions were assessed by methods of stabilography, electromyography and tremorometry; besides, accuracy of target shooting was registered. Results: high degree of shooting accuracy dependence on posture somatic parameters has been revealed, of which the greatest impact upon the result is exerted by low-frequency vibrations of the body general centre of mass, subjected to voluntary control. Prognostic models of shooting accuracy dependence upon the character of posture regulation during ready position and the shot have been developed. Conclusions: obtained results reveal the mechanisms of functioning and interacting of two systems of management - posture and voluntary motion. Elaborated regression models permit to model and predict posture stability and shooting accuracy during ready position and the shot.